Postsecondary Education as Triage: Returns to Academic and Technical Programs - Kevin Hollenbeck (W.E. Upjohn Institute for Employment Research, 1992)
This paper examines the labor market outcomes of individuals with various types of postsecondary educational experiences. In particular, it examines differences between students who have pursued technical education programs from those who have pursued academic programs and from those individuals who have not pursued any type of postsecondary education. Empirical evidence is presented concerning the relationship between economic outcomes and grades earned and the degree to which the labor market rewards credentials. Wage and earnings models yield different structural parameter estimates when based on the three different populations. The differences are most dramatic for high school background effects and for postsecondary characteristics. The empirical results from the technique used to correct for self-selection suggest that individuals' choices into the three postsecondary tracks are not the result of absolute advantage.
Keywords: J0; I2; 330; postsecondary; education; labor; market; outcomes; Hollenbeck